PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENGEMBANGKAN CIVIC SKILL SISWA SEKOLAH DASAR - Haifarashin, Ridha; Kurniawati; Furnamasari, Yayang Furi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low implementation of civic skills due to the continued use of conventional learning methods and the absence of a combination of varied learning methods. So that students are less active in learning and the implementation of civic skills is not optimal. This study aims to determine the effect of the application of the creative problem solving (CPS) model on the development of civic skills of elementary school students in Pancasila Education learning on cultural diversity material in grade V. The method used in this study is quantitative with a quasi-experimental non-equivalent control group design. The results showed that there was a significant effect of the application of the creative problem solving model in improving students' civic skills, as evidenced by the difference in pretest and posttest scores between the experimental and control classes. The average posttest score of the experimental class (85.32) was higher than the control class (78.73). The paired sample t-test produced a sig. value of 0.000 (<0.05), confirming that the creative problem solving model is effective in improving students' civic skills. In addition, the independent sample t-test on the posttest showed a significant difference (sig. 0.021 < 0.05) between the experimental and control classes, indicating that the creative problem solving model is more effective than the cooperative learning model of the group investigation type. Thus, the creative problem solving model is able to improve students' civic skills more optimally than the cooperative learning model of the group investigation type.